Parameter Analysis of Pile Foundation Bearing Characteristics Based on Pore Water Pressure Using Rapid Load Test - Jing-Jie Su; Xue-Liang Zhao; Qing Guo; Wei-Ming Gong; Yu-Chen Wang; Tong-Xing Zeng (Infrastructures)
A novel approach for determining the bearing capacity of pile foundations using rapid load testing is suggested to rectify the inaccuracies arising from the presumption of a constant damping coefficient and excess pore water pressure during the evaluation of pile foundation bearing capacity in soil. This research focuses on the characteristics associated with the segmented damping coefficient of pile foundations and the permeability coefficient of sand at the pile terminus, resulting in a long pulse vibration equation derived from dynamic effects. A numerical model incorporating the damping coefficient and permeability coefficient is developed, yielding the time history features of load, displacement, and acceleration. The findings indicate that (1) the long pulse vibration equation, predicated on dynamic effects, aligns more closely with the actual bearing capacity of pile foundations than traditional detection theory; (2) in the rapid load test method, the maximum load applied to sand pile foundations occurs prior to peak displacement, while the ultimate bearing capacity, after accounting for inertial forces, corresponds to the maximum displacement value; (3) the permeability coefficient significantly influences the ultra-static pore water pressure, and the testing error regarding the bearing capacity of low permeability sand pile foundations using the rapid loading method is elevated.